Boosting the Intention to Purchase Online: An analysis of e-service quality among customers - Abd Rashid, Muhammad Hafiz; Suhaimi, Nurhazirah; Humaidi, Norshima; Gita Gayatri (Environment-Behaviour Proceedings Journal, 2023)
This study intends to investigate the impact of e-service quality on Malaysian customers’ propensity to make online purchase. Data collection was performed by distributing questionnaires to online shoppers in Klang Valley, Malaysia by employing purposive sampling technique. A total of 212 questionnaires were usable for data analysis by using PLS-SEM method. According to the findings, the likelihood to purchase online was positively impacted by all the e-service quality dimensions namely trust, shopping enjoyment, website design, and privacy. This study also discusses the practical implications and put forward several recommendations to be considered by future researchers.